Conservative management of women with cervical intraepithelial neoplasia grade 2 in Denmark: a cohort study. (22nd January 2020) - Skorstengaard, M; Lynge, E; Suhr, J; Napolitano, G
Abstract : Objective: Assess the progression, persistence, and regression of cervical intraepithelial neoplasia grade 2 (CIN2) after new guidelines on conservative treatment, compared with previous practice. Design: Nationwide register‐based cohort study. Setting: Denmark. Population: Women aged 18–44 years diagnosed with CIN2 on biopsy: 6721 in 2008–2011 and 6399 in 2014–2017. Methods: Register data were retrieved from before (2008–2011) and after (2014–2017) the introduction of new guidelines. Histology diagnoses at second visit were used to assess progression (CIN3+), persistence (CIN2), or regression (CIN1/normal). Main outcome measures: Proportion of CIN2 by type of management. Relative risk (RR) and corresponding 95% confidence intervals (95% CIs) for progression, persistence, and regression at second visit in 2014–2017, versus 2008–2011. Results: The proportion of CIN2 managed conservatively increased from 29.6% in 2008–2011 to 53.3% in 2014–2017 (RR 1.81, 95% CI 1.73–1.89). Time to second visit increased by 2 months. Regression increased from 23.5 to 30.2% (RR 1.29, 95% CI 1.22–1.36), whereas persistence and progression decreased, from 42.6 to 34.9% (RR 0.82, 95% CI 0.78–0.86) and from 28.0 to 22.8% (RR 0.81, 95% CI 0.77–0.86), respectively. In 2008–2011, women managed conservatively had a regression rate of 41.8%, persistence rate of 40.9%, and progression rate of 16.6%. In 2014–2017, these rates were 46.7, 35.5, and 17.1%, respectively. Conclusion: After implementation of the new guidelines, conservative management became more frequent, and is now used for more than half of women with CIN2. Lesion regression became more frequent, now experienced by 47% of women managed conservatively. Similar regression rates were seen in women younger and older than 30 years, suggesting that conservative management is justifiable for women of childbearing age. Tweetable abstract: In Denmark, more than half of women with CIN2 are managed conservatively, and half of these women experience lesion regression. Tweetable abstract: In Denmark, more than half of women with CIN2 are managed conservatively, and half of these women experience lesion regression.